Spectrophotometric Study of ?-Irradiated PM-355 (Baghdad Science Journal, 2009)
The aim of the present work is concerned with the effect of ?-irradiation on PM-355 with absorbed dose of (30-160Mrad) range. This polymer is evaluated spectrophotometrically for use as high dose dosimeters. The absorption spectra of irradiated samples showed radiation induced absorption changes. There is an increment in absorption proportional with absorbed dose. This increment is attributed to interfaces traps which, are formed by irradiation. Calibration curve was drawn .The linear relation was found in calibration curve, and dosimeter range was determined from the linear part. The linearity in response curve suggested that PM-355 could be used as dosimeter within (30-160Mrad) rang. Energy gap shift was used as a second tool to determine the dosimeter range. It was found that PM-355 energy gap systematically decreasing with absorbed dose, and it could be used as a second tool to determine the dosimeter range.